The Mediating Role of Work Discipline in the Relationship between Teacher Competence, Motivation, and Performance - Helyna Riskawaty; Ambo Sakka; Suhaimi Suhaimi (Edunesia : Jurnal Ilmiah Pendidikan, 2026)
This research investigates the mediating role of work discipline in the relationship among teacher competence, work motivation, and teacher performance at state junior high schools in Pulau Laut Utara District, Kotabaru Regency. A quantitative research design employing SEM-PLS analysis was adopted, with data gathered from 102 teachers drawn via proportional random sampling from a total population of 134. Findings reveal that teacher competence exerts a positive and significant impact on both work discipline and teacher performance, whereas work discipline substantially enhances performance and serves as a mediator for the effect of competence. Work motivation similarly produces a positive influence on discipline; however, its direct contribution to performance is negative, though it still yields a positive outcome on performance when channeled through discipline. The structural model demonstrates remarkably high explanatory capacity, with R² values reaching 0.913 for work discipline and 0.927 for teacher performance. These outcomes underscore that elevating teacher performance demands not merely the reinforcement of professional competence, but equally the cultivation of disciplined workplace conduct and the strategic management of motivation via supportive oversight mechanisms. This study yields actionable recommendations for educational administrators and policymakers in regional settings committed to sustainable advancement of educational quality.